The Effect of Healing Touch Therapy on Anxiety: Systematic Literature Review - Ramlah Ramlah; Yunie Armiyati; Mohammad Fatkhul Mubin (Indonesian Journal of Global Health Research, 2025)
Patient anxiety that is not handled properly can have an impact on the patient's deterioration in health status and quality of life. One of the therapies that can be applied is to overcome patients' anxiety disorders with touch healing therapy. . One therapy that can be applied to address anxiety disorders in patients with anxiety disorders is healing touch therapy. The purpose of this literature review was to determine the effect of healing touch therapy on anxiety. This literature review was conducted through a search of publications in Google Scholar, Somantic Scholar Proquest, and PubMed between 2019 and 2025 using the PRISMA method. The keywords used were "Healing Touch" OR "Therapeutic Touch" AND Anxiety OR "Anxiety Disorders". The search for related articles from seven sources met the inclusion criteria, the results of the search for articles from several sources obtained 170 articles, of which only 6 articles met the criteria. The conclusion was that healing touch therapy has an effect on patient anxiety. Healing touch therapy is an intervention that can be implemented or carried out by nurses to help reduce patient anxiety levels.